Prognostic role of pre-diagnostic circulating inflammatory biomarkers in breast cancer survival: evidence from the EPIC cohort study - Castro-Espin, C; Cairat, M; Navionis, A; Dahm, CC; Antoniussen, CS; Tjønneland, A; Mellemkjær, L; Mancini, FR; Hajji-Louati, M; Severi, G; Le Cornet, C; Kaaks, R; et al. (Springer Nature [academic journals on nature.com], 2024)
Background: Inflammation influences tumour progression and cancer prognosis, but its role preceding breast cancer (BC) and its prognostic implications remain inconclusive. Methods: We studied pre-diagnostic plasma inflammatory biomarkers in 1538 women with BC from the EPIC study. Cox proportional hazards models assessed their relationship with all-cause and BC-specific mortality, adjusting for tumour characteristics and lifestyle factors. Results: Over a 7-year follow-up after diagnosis, 229 women died, 163 from BC. Elevated IL-6 levels were associated with increased all-cause mortality risk (HR1-SD 1.25, 95% CI 1.07–1.47). Among postmenopausal, IL-6 was associated with higher all-cause (HR1-SD 1.41, 95% CI 1.18–1.69) and BC-specific mortality (HR1-SD 1.31, 95% CI 1.03–1.66), (PHeterogeneity (pre/postmenopausal) < 0.05 for both), while IL-10 and TNFα were associated with all-cause mortality only (HR1-SD 1.19, 95% CI 1.02–1.40 and HR1-SD 1.28, 95% CI 1.06–1.56). Among ER+PR+, IL-10 was associated with all-cause and BC-specific mortality (HR1-SD 1.35, 95% CI 1.10–1.65 and HR1-SD 1.42 95% CI 1.08–1.86), while TNF-α was associated with all-cause mortality in HER2- (HR1-SD 1.31, 95% CI 1.07–1.61). An inflammatory score predicted higher all-cause mortality, especially in postmenopausal women (HR1-SD 1.30, 95% CI 1.07–1.58). Conclusions: Higher pre-diagnosis IL-6 levels suggest poorer long-term survival among BC survivors. In postmenopausal survivors, elevated IL-6, IL-10, and TNFα and inflammatory scores seem to predict all-cause mortality.